1996
DOI: 10.1042/cs0900097
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation and Heart Rate Variability

Abstract: 1. Heart rate variability is modulated by multiple control systems, including autonomic and hormonal systems. Long-term variability, i.e. the very low-frequency band of the power spectra, has been postulated to reflect thermoregulatory vasomotor control, based upon thermal entrainment experiments. However, the relationship between thermoregulatory responses (vasoconstriction and shivering) and heart rate variability has not been studied. 2. We performed two distinct protocols in a series of human subjects. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
70
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 34 publications
7
70
0
Order By: Relevance
“…21) Changes in temperature regulation and the neuroendocrine system related to stress do occur postoperatively as well and could have also influenced HRV. 19,22) Immobility per se is unlikely to be of significance.…”
Section: Discussionmentioning
confidence: 99%
“…21) Changes in temperature regulation and the neuroendocrine system related to stress do occur postoperatively as well and could have also influenced HRV. 19,22) Immobility per se is unlikely to be of significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, single reports from experimental studies are available. For example, Fleisher et al [27] demonstrated that the decreased temperature was associated with the increased VLF power spectrum…”
Section: Discussionmentioning
confidence: 99%
“…Fleisher et al [31]showed that power at very low frequencies increases when reducing the core temperature of normal subjects, but remains unchanged when skin temperature is increased or decreased, thus suggesting a specific thermoregulatory influence on this component related to core hypothermia. To our knowledge, no data on the change of very-low-frequency power at increase of core temperature exist.…”
Section: Discussionmentioning
confidence: 99%